2014
DOI: 10.1292/jvms.13-0423
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Indicator Bacteria Isolated from Chickens in Southeast Asian Countries (Vietnam, Indonesia and Thailand)

Abstract: To determine the prevalence of indicator bacteria resistant to antimicrobials among poultry in three Southeast Asian countries (Vietnam, Indonesia and Thailand), we examined the antimicrobial susceptibilities of commensal bacteria isolated from chickens. In total, 125, 117 and 180 isolates of Escherichia coli, Enterococcus faecalis and Enterococcus faecium, respectively, were used to test for antimicrobial susceptibility. Bacterial resistance to antimicrobial treatment was most frequently observed with oxytetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
(37 reference statements)
9
39
0
Order By: Relevance
“…However, in the PCR analyses, none of these enterococci was found to have vancomycin resistance genes. Similarly, Usui et al (14) in their study in which they found low susceptibility to vancomycin (8 mg/L) in 4 isolates could not detect vanA and vanB resistance genes in these isolates. Therefore, it is evident that phenotypic tests alone are not sufficient to determine vancomycin resistance and that vancomycin resistance genes should also be identified.…”
Section: Discussionmentioning
confidence: 80%
“…However, in the PCR analyses, none of these enterococci was found to have vancomycin resistance genes. Similarly, Usui et al (14) in their study in which they found low susceptibility to vancomycin (8 mg/L) in 4 isolates could not detect vanA and vanB resistance genes in these isolates. Therefore, it is evident that phenotypic tests alone are not sufficient to determine vancomycin resistance and that vancomycin resistance genes should also be identified.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, high resistance to enrofloxacin can be associated with the administration of this drug at a therapeutic level for short periods of time or for preventive use in growing broilers. Resistance to fluoroquinolones was frequently observed in E. faecium (82.8%) and E. faecalis (17.9%) in countries of Southeast Asia (Usui et al, 2014). According to Maasjost et al (2015), fewer isolates, numbering 7 (5%) of E. faecalis and 10 (56%) of E. faecium from the internal organs of poultry, demonstrated resistance to ciprofloxacin.…”
Section: Enterococcus Faecalis (%)mentioning
confidence: 99%
“…The large importers of livestock, mainly cattle and pigs, are Singapore, Malaysia, and Indonesia (24). Studies carried out in Malaysia, Thailand, Vietnam, Indonesia, and other Southeast Asian countries reported MDR enterococci isolated from livestock and animal-related products (23,25). Many Southeast Asian nations, such as Malaysia, Myanmar, Indonesia, Thailand, and Vietnam, have flourishing poultry and livestock industries and are also major exporters around the Asian region (26).…”
Section: Nonhuman Reservoirs Of Enterococcus Sppmentioning
confidence: 99%
“…Although there is a large amount of data about the emergence of antimicrobial-resistant enterococci in Southeast Asian countries, most of this information is fragmented since it has been published in different papers in different countries over several decades (41)(42)(43)(44). However, several studies show the extent of unregulated and inappropriate use of antimicrobials in food animals in developing Southeast Asian countries such as Vietnam and Malaysia (23,25,45). Usui et al (25) obtained results that demonstrate the use of antimicrobials in chickens in Southeast Asian countries, especially Vietnam, to be higher than in developed countries (45).…”
Section: Use Of Antimicrobials In Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation